2011
DOI: 10.1521/soco.2011.29.3.238
|View full text |Cite
|
Sign up to set email alerts
|

The Mental Roots of System Justification: System Threat, Need for Structure, and Stereotyping

Abstract: In a series of correlational and experimental studies, it is shown that system justifi cation motives result in stereotyping and that an important force behind this effect is an increased need for structure. People who perceive the system they are part of (e.g., their company) as unfair report a higher need for structure and are more likely to engage in stereotyping. Second, experimentally induced system threat increased structure needs which covaried with amplifi ed negative and positive stereotyping effects,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Participants were led to believe that the computer would present a series of unrelated studies in random order, including an information processing study and several short pilot studies to help the researchers design materials for later in the semester. In fact, the fi rst task always manipulated system justifi cation motivation using a procedure developed by Jost and colleagues (Jost, Kivetz, Rubini, Guermandi, & Mosso, 2005, Study 3; see also Kay et al, 2005;Lau, Kay, & Spencer, 2008;Stapel & Noordewier, 2011). Research has shown that although this manipulation has a highly signifi cant effect on participants' perceptions of the social system, it has no effect on measures of individual or collective self-esteem (Kay et al, 2005(Kay et al, , 2009Wakslak, Jost, & Bauer, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Participants were led to believe that the computer would present a series of unrelated studies in random order, including an information processing study and several short pilot studies to help the researchers design materials for later in the semester. In fact, the fi rst task always manipulated system justifi cation motivation using a procedure developed by Jost and colleagues (Jost, Kivetz, Rubini, Guermandi, & Mosso, 2005, Study 3; see also Kay et al, 2005;Lau, Kay, & Spencer, 2008;Stapel & Noordewier, 2011). Research has shown that although this manipulation has a highly signifi cant effect on participants' perceptions of the social system, it has no effect on measures of individual or collective self-esteem (Kay et al, 2005(Kay et al, , 2009Wakslak, Jost, & Bauer, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Family System Justification that have been examined with respect to the rationalization of societal institutions are also at work in families, friendship networks, and other small-scale social systems such as work teams and organizations (see also Stapel & Noordewier, 2011). Second, the evidence of spreading rationalization that we have obtained points to previously unexplored psychological associations among social systems as diverse as the nation, the high school popularity hierarchy, and the nuclear family.…”
Section: American System Justificationmentioning
confidence: 69%
“…However, it is possible that threats directed at the social systems to which one belongs are experienced as direct threats to the self-concept. Indeed, we assume that various social systems and institutions are represented by the individual as part of the status quo, and they confer a sense of order and stability for the individual; this is why questioning their legitimacy and stability is psychologically threatening (see also Stapel & Noordewier, 2011). At the same time, it should be pointed out that in Experiment 2 system threat did not affect self-esteem, as other theoretical perspectives might have assumed (e.g., Pyszczynski, Greenberg, Solomon, Arndt, & Schimel, 2004).…”
Section: American System Justificationmentioning
confidence: 88%
See 2 more Smart Citations